Detecção e quantificação de Salmonella spp. por PCR em tempo real em amostras de abatedouros avícolas - Martelo, Eduarda Boff (2016)
The genus Salmonella is responsible for a zoonosis known as salmonellosis and consumption of poultry products is implicated as a major source of infection for humans. The association between Salmonella spp. in poultry and enteritis in humans arises from the persistence of the agent in broiler habitat, which provides the asymptomatic intestinal colonization in the bird while the improper handling of raw meat and the consumption of undercooked meats are risk factors for foodborne illness. Methods for rapid diagnosis, s ensitive and specific, allowing not only detecting but also the quantification of bacteria are required for both the food industry and for the regulators and real time PCR is an alternative to conventional methods for estimating Salmonella. In this work we used real-time PCR to identify and quantify contamination by Salmonella spp. since the arrival of poultry to the final product in slaughterhouses under federal inspection. The selected samples were previously collected from different parts of the slaughter technology and considered positive for Salmonella by microbiological techniques: conventional microbiology (CM) and miniaturized Most Probable Number (mMPN), which configured the batch as positive for the agent. Were evaluated 139 samples in 5 batches, of which 27 (19%) were positive by conventional microbiology and mMPN and 68 (49%) by real-time PCR, setting the sensitivity of the technique. Within batch contamination varies from 1.93 log 10 CFU / mL to 7.99 log 10 CFU / mL, and most contamination was tested in a collecting cage after its cleaning swab (7.99 log 10 CFU / mL) and the least contamination was found in a frozen carcass at -12oC to 24 hours (1.93 log 10 CFU / mL). These results allow inferring that contamination by Salmonella spp. in slaughterhouses is variable, but generally, the poultry arrive at the slaughterhouse with a level of contamination that is reduced along the slaughter technology, emphasizing the importance of biosecurity at the farms and the application of good manufacturing practices in slaughterhouses.